2010
DOI: 10.1111/j.1365-2621.2009.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chickpea on the functional properties of white and whole wheat bread

Abstract: The effects of the addition of chickpea (Cicer arietinum), emulsifier and altered amount of water on the functional properties (bread volume, colour of crust, crumb texture and crumb porosity) of white and whole wheat bread were investigated applying a screening three factorial design. Addition of chickpea increased crumb firmness and slightly decreased bread volume in both bread types. Addition of emulsifier increased bread volume and decreased bread firmness. Altering the amount of water addition had no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 20 publications
3
30
0
2
Order By: Relevance
“…The bread volume is related to the quantity and quality of gluten (Chloupek et al 2008;Rosell et al 2009). Bread volume is measured as one of the most important criteria in evaluating bread quality (Yamsaengsung et al 2010). Our study showed that the specific volume values of whole wheat bread were increased by the additional materials (Figure 2).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The bread volume is related to the quantity and quality of gluten (Chloupek et al 2008;Rosell et al 2009). Bread volume is measured as one of the most important criteria in evaluating bread quality (Yamsaengsung et al 2010). Our study showed that the specific volume values of whole wheat bread were increased by the additional materials (Figure 2).…”
Section: Resultsmentioning
confidence: 70%
“…The decrease in the crumb firmness can be explained by the increase in the loaf volume as well as the improvement in the crumb characteristics. It was been stated that the increased loaf volume is directly related to the decreased firmness values which is due to an increased probe-to-crust distance as the loaf volume increased (Wanga et al 2002;Yamsaengsung et al 2010). Looking at the materials in the treatments, it can be stated that DCSF and vital gluten have positive effects on both the crumb firmness and the loaf volume.…”
Section: Resultsmentioning
confidence: 99%
“…; Yamsaengsung et al . ). Char magaz composition is about 6% fat, 18% protein and 60% carbohydrate (Okigbo et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the case of the lentil protein supplemented bread, no significant difference was observed between the 3 and 6% supplementation levels and no significant difference was observed between the 6 and 9% supplementation levels for the pea protein supplemented breads (Figure 6b). Yamsaengsung et al (2010) studied the effects of the addition of chickpea flour (Cicer arietinum) on the color of the crust of white and whole wheat bread. They reported that in white bread, chickpea addition increased darkness and yellowness of the bread.…”
Section: Color Measurementmentioning
confidence: 99%